The ratio of osteocytic incorporation to bone matrix formation in femoral neck cancellous bone: an enhanced osteoblast work rate in the vicinity of hip osteoarthritis. - Jordan, G; Loveridge, N; Power, J; Clarke, M; Parker, M; Reeve, J (2003)
Recently it has been shown that an inactivating mutation in the TGFb-SMAD3 signaling pathway, which increases the conversion of osteoblasts to osteocytes, is accompanied by bone loss combined with increased osteocyte density. We hypothesized that increased matrix TGFb, known to occur in osteoarthritis, might cause the reverse of these effects in man. Because coxarthrosis (cOA) is associated with a reduced risk of femoral neck fracture, whole cross-section femoral neck biopsies were obtained from 11 patients with femoral neck fracture, 14 patients with cOA, and 22 age-and sex-matched controls. Lacunar density (Lc x mm2), osteocyte density (Ot x mm2), and cancellous wall width (Cn x W x Wi), were compared between cases of coxarthrosis, femoral neck fracture (FNF) and controls. In cOA, Lc.mm2 was reduced by 24% (P <0.001) while in FNF it was increased by 20% (P <0.001). Cn x W x Wi was increased in cOA by 22% (P <0.05) and in FNF was reduced by 27% (P <0.001). Lc x mm2 was inversely related to percentage cancellous bone area (adj. r2 = 0.373; P <0.01) and wall widths, r2 = 0.382, P <0.001. The reduction in osteocyte lacunar density coupled with increased wall width is consistent with a model of cOA effects on bone in which increased levels of matrix TGFb might prolong the effective lifespan or work rate of the osteoblast and delay its incorporation into the matrix as an osteocyte. One possible approach to strengthening bone in osteoporosis might be to enhance the effective lifespan of the osteoblast by modulating TGFb-related pathway activity in its local environment.